AAR553: Structural Theories And Applications / Faculty of Architecture, Planning & Surveying - UiTM, Faculty of Architecture, Planning & Surveying (Universiti Teknologi MARA (UiTM), 2023)
This course covers the application of structural theories in architecture and building. The topics cover the study of forces, section properties, and strength of materials and analysis of main building components including roof structure, columns and beams.